Tinjauan Kriminologis Terhadap Tindak Pidana Penelantaran Anak Oleh Orang Tua - Fitriya Wardhany, Nyimas Enny (Universitas Batanghari Jambi, 2024)
Children are a gift of God Almighty in which there is also a dignity and dignity possessed by adults in general, so children must also receive special protection so that they can grow and develop properly, because children are the next generation of the nation and play a role in ensuring the continued existence of a nation and state itself. This child neglect still occurs in many communities whose economy is experiencing problems or experiencing shortages. The results of this study indicate that there is still a lot of child neglect, which is caused by economic factors, parents who experience divorce, and environmental factors. The obstacles faced are difficulties in collecting evidence, parties who are difficult to call, the absence of public complaints about child neglect that occurs around them. Then preventive efforts are made and repressive efforts are also made by taking direct action.